Obstructive Sleep Apnea and Hearing Loss: Is There Any Correlation? - Chauhan, Pankaj; Guleria, Trilok Chand; Sharma, Sunil; Minhas, Ravinder S.; Dadwal, Madhuri; Mohindroo, Narender K. (International Archives of Otorhinolaryngology, 2022)
Introduction Obstructive sleep apnea (OSA) is a breathing disorder related to sleep that has a negative effect on the behavior and health of people around the globe. Chronic hypoxemia and variations in the concentration of oxygen in the blood noticed in OSA individuals may have adverse effects on the process of auditory transduction and transmission.Objective To assess the effect of OSA on hearing and to find out the parameters that have more influence on hearing recorded during polysomnography of patients with OSA.Methods The present is a hospital-based, observational, analytical, cross-sectional study conducted over a period of one year. After application of the exclusion criteria, the patients were then submitted to the application of the Berlin questionnaire, as well as polysomnography, impedance, and pure tone audiometry (PTA).Results A total of 58 individuals were studied. Age, gender, and height were comparable among cases and controls, while weight, body mass index (BMI), and neck circumference were significantly higher in cases in comparison to controls. The mean PTA was significantly higher at 10 kHz or higher frequencies in cases in comparison to controls.Conclusion We observed that there is evidence that the auditory mechanism is affected in OSA patients. We recommend early auditory screening of OSA patients for timely diagnosis and to raise awareness about its prevention.
Keywords: sleep apnea; obstructive sleep apnea; polysomnography; audiometry